The Factors Affecting Budget Absorption of Regional Apparatus Work Units in Payakumbuh City Government with Budget Changes as Moderating Variables - suseno, indra (ADPEBI, 2022)
This study aims to analyze the factors that influence the absorption of the Regional Apparatus Work Unit budget at the Payakumbuh City Government with budget changes as a moderating variable. The type of research conducted is causal associative which is quantitative. The research method uses a survey method. The population in this study is the Financial Administration Officer and treasurer in all Regional Apparatus Work Units at the Payakumbuh City Government, totaling thirty one Regional Apparatus Work Units. The entire population was used as a sample of sixty-two people. The data was processed using the Statistical Package for Social Science (SPSS) application for the results of multiple regression analysis and residual tests. The results of this study prove that simultaneously planning, administration, human resources, procurement documents, and reimbursement have a positive and significant effect on budget absorption, but partially the variables of planning, administration, human resources, procurement documents, and reimbursement have a positive effect but not significant to the budget absorption of the Regional Apparatus Work Unit at the Payakumbuh City Government. Changes in the budget as a moderating variable have a positive effect but are unable to moderate the relationship between planning, administration, human resources, procurement documents and reimbursement of the budget absorption of the Regional Apparatus Work Unit in Payakumbuh Government.